The prosody of focus - Stopar, Andrej (Linguistica (Ljubljana), 2017)
The article presents an approach to information structure that marks focused or topicalized syntactic constituents with the features FOC and TOP, and assumes that the assignment of these information structure features is reflected in prosody. The experimental study measures the fundamental frequency of various Slovenian sentences to identify the characteristic contours of the non-contrastive, contrastive, and verum focus. The findings are compared to those in studies on English and Russian. The results show that the most relevant prosodic characteristics of such structures are the pitch range, the pitch changes on the focus exponent, and the duration of the focus exponent.
Keywords: angleščina; English; intonacija; primerjalna analiza; prozodija; Russian; ruščina; Slovene; slovenščina